Pelaksanaan Manajemen Berbasis Madrasah Dalam Upaya Peningkatan Kualitas Pendidik Dan Tenaga Kependidikan Di MAS PP Nuruddin Riau - Riko Tampati; M. Damrah Khair; Sri Lestari (Najah Bestari, 2023)
The quality of the workforce employed by an organization has a significant influence on the level of profitability of the organization. Likewise, the success of schools and madrasas is also determined by the managers who run them. If the management of the school or madrasah is of high quality, then the institution will progress and maintain its quality, and vice versa. Therefore, the purpose of this article is to describe the management of improving the quality of labor and human resources, namely MAS PP Nuruddin Sungai Sarik, Kampar Kiri District, Kampar Regency, which is the object of this research study. Planning, recruitment, training and employee development, promotion, transfer and termination of employees, as well as employee evaluation and compensation at MAS PP Nuruddin Sungai Sarik, Kampar Kiri District, Kampar District are the main concerns of this research. Through observation, interviews and documentation it is known that human resource management is running well at least meeting the requirements set by the government.